The Takror Method for Improving Qur’an Memorization Abilities of Pesantren Students - Zainal Arifin; Muhammad Yusron Maulana El-Yunusi (Sekolah Tinggi Ilmu Tarbiyah Togo Ambarsari, 2026)
This study aims to analyze the planning, implementation, and the supporting and hindering factors of The Takror Method for enhancing Qur’an memorization among tenth-grade students. The method, a strategy in Qur’an memorization through regular repetition, strengthens memorization, minimizes mistakes, and helps students maintain their memorization in the long term. A descriptive qualitative approach with a case study design was used in this research. Data were collected through observation, interviews, and documentation, and analyzed using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing, with triangulation for validation. The findings revealed that the planning of the method was systematically structured through teacher guidance and a well-organized schedule. The implementation of the method to enhance the memorization skills of the students involved several stages, including reading the Qur’an repeatedly, memorizing incrementally, recalling without the mushaf, integrating memorized verses, reviewing old memorization, and presenting the memorization to the teacher. Supporting factors included student discipline, active teacher involvement, a conducive environment, a structured memorization schedule, and internal motivation. However, hindering factors consisted of differences in students' baseline abilities, monotony from repetition, time limitations, inconsistent independent review, and psychological challenges. Future research could explore ways to overcome these obstacles and investigate the long-term impact of the method on Qur’an memorization.